2016
DOI: 10.3109/00952990.2016.1168430
|View full text |Cite
|
Sign up to set email alerts
|

Coadministration of disulfiram and lorazepam in the treatment of alcohol dependence and co-occurring anxiety disorder: an open-label pilot study

Abstract: Background Anxiety is common among persons with alcohol use disorder during early abstinence from alcohol. Although benzodiazepines are effective for short-term treatment of anxiety, they are rarely used beyond acute detoxification due to concerns about misuse or interactions with alcohol. Objectives We conducted an open-label trial to explore the effects of coadministering lorazepam and disulfiram to alcohol dependent patients with anxiety disorder symptoms. The rationale for this model is to minimize the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
6
2
Order By: Relevance
“…Findings from a recent open‐label trial including 41 AUD patients were partly consistent with ours. It found that disulfiram plus lorazepam could significantly increase the percent abstinent days and reduce depressive symptoms 96 . However, in our study, disulfiram showed no benefit to depressive symptoms compared to controls, indicating the need for combination with medication specifically targeting depressive symptoms.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Findings from a recent open‐label trial including 41 AUD patients were partly consistent with ours. It found that disulfiram plus lorazepam could significantly increase the percent abstinent days and reduce depressive symptoms 96 . However, in our study, disulfiram showed no benefit to depressive symptoms compared to controls, indicating the need for combination with medication specifically targeting depressive symptoms.…”
Section: Discussioncontrasting
confidence: 77%
“…As one of the earliest approval medications for alcoholism, in our study, disulfiram was demonstrated to be the most efficacious 96 However, in our study, disulfiram showed no benefit to depressive symptoms compared to controls, indicating the need for combination with medication specifically targeting depressive symptoms. By extendedly blocking the acetaldehyde dehydrogenase, disulfiram could trigger uncomfortable "Antabuse" reactions such as tachycardia, flushing, and nausea after drinking, which gradually established the aversion to alcohol and finally achieve the aim of quitting drinking.…”
Section: Discussioncontrasting
confidence: 57%
“…A previous clinical study indicated that DSF was more effective than a placebo and as effective as the benzodiazepine anxiolytic chlordiazepoxide at reducing anxiety in alcoholic outpatients ( Rosenberg, 1974 ). Another study indicated that coadministration of DSF and lorazepam to alcoholic patients with co-occurring anxiety disorder largely reduced anxiety, depression, and cravings ( Bogenschutz et al, 2016 ). However, other investigations reported no statistically significant anxiolytic effects attributable to DSF in alcoholics ( Snyder and Keeler, 1981 ; Goyer et al, 1984 ).…”
Section: Discussionmentioning
confidence: 99%
“…The medications recommended to treat alcohol use disorders (AUD) in Brazil are the same as those approved by the Food and Drug Administration (FDA): disulfiraminhibits acetaldehyde dehydrogenase; naltrexone -blocks µ-opioid receptors; and acamprosate -blocks N-methyl-D aspartate glutaminergic receptors (Williams, 2005;Bogenschutz et al, 2016;Walker et al, 2019;Jorgensen, Pedersen, Tonnesen, 2011;Campana et al, 2012). These medications are recommended to control the desire and / or urge to drink, in addition to psychosocial monitoring (Campana et al, 2012).…”
Section: Pharmacotherapy Used For Alcohol and Cocaine Use Disorders I...mentioning
confidence: 99%